Evaluation of Gadolinium Pre-Treatment with or without Splenectomy in the Setting of Renal Ischemia Reperfusion Injury in Rats - ATA, PINAR; ÇETİNEL, ŞULE (TAYLOR & FRANCIS LTD, 2009)
Introduction. This study aims to investigate gadolinium chloride (Gd) pre-treatment with/without splenectomy (Splx) in the setting of renal ischemia/reperfusion (IR) injury in rats. Materials and Methods. Under anesthesia, male Wistar albino rats with or without splenectomized (Splx) were right nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 3 h of reperfusion. Gadolinium chloride (10 mg kg(-1)) or saline was administered 24 hours prior to ischemia via penile vein. Right nephrectomy and intravenous saline administration was performed in the control group. At the end of the reperfusion period, following decapitation, kidney samples were taken for histological examination or determination of renal malondialdehyde (MDA) and glutathione (GSH) levels and myeloperoxidase (MPO) and Na+-K+ ATPase activities. Creatinine, blood urea nitrogen (BUN), lactate dehydrogenase (LDH), TNF-alpha, and IL-1 beta were assayed in the serum samples. Results. Ischemia/reperfusion caused significant increases in the serum TNF-alpha, IL-1 beta, BUN, creatinine, AST, ALT, LDH, and tissue MDA levels and MPO activity, while either Gd pre-treatment or Splx decreased these parameters significantly. On the other hand, IR induced a decrease in the tissue GSH, and Na+-K+ ATPase activity was restored by both gadolinium and Splx. Furthermore, histopathological alterations induced by IR were also reversed. Conclusion. The extent of renal IR injury depends on the pro-inflammatory cytokine response. Gd pretreatment decreases macrophage-derived cytokine secretion and thereby effectively limits the extent of renal IR injury in rats similar to Splx. Further studies needed to define an optimal way of decreasing macrophage-derived cytokine release due to the clinical limitations of Gd.
Keywords: renal ischemia reperfusion; gadolinium chloride; splenectomy; pro-inflammatory cytokine; INTESTINAL ISCHEMIA; ISCHEMIA/REPERFUSION INJURY; CONTRAST AGENTS; FREE-RADICALS; NITRIC-OXIDE; FAILURE; LIVER; KIDNEY; MACROPHAGES; GLUTATHIONE